Languages, Design Methods, and Tools for Electronic System Design Selected Contributions from FDL 2017 - Große, Daniel; Vinco, Sara; Patel, Hiren (Lecture Notes in Electrical Engineering,, 2019)
This book brings together a selection of the best papers from the twentiethedition of the Forum on specification and Design Languages Conference (FDL), which took place on September 18-20, 2017, in Verona, Italy. FDL is a well-established international forum devoted to dissemination of research results, practical experiences and new ideas in the application of specification, design and verification languages to the design, modeling and verification of integrated circuits, complex hardware/software embedded systems, and mixed-technology systems. Covers modeling and verification methodologies targeting digital and analog systems; Addresses firmware development and validation; Targets both functional and non-functional properties; Includes descriptions of methods for reliable system design.